2022
DOI: 10.1186/s12889-022-12904-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training about child neglect and abuse to teachers and its effect to awareness

Abstract: Background This study aimed to evaluate the effects of child neglect and abuse training on the knowledge and awareness of medical vocational schoolteachers in Turkey. Methods This study was conducted based on data taken from a sample of teachers from Kayseri, Turkey, between October 2016 and April 2017. Teachers who agreed to participate in the study received training pertaining to child neglect and abuse. Data were collected through a survey form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Based on the findings of a recent systematic study, it has been established that the mistreatment of children might have negative consequences for the children, which may hinder their overall development [ 37 , 38 , 39 , 40 , 41 ]. The scenario will be completely different in European countries, Middle Eastern countries, North American countries, and the Indian subcontinent [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. A Chinese group also highlighted the need to focus resources on child safety and improve national knowledge of child abuse in China based on a systematic review [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings of a recent systematic study, it has been established that the mistreatment of children might have negative consequences for the children, which may hinder their overall development [ 37 , 38 , 39 , 40 , 41 ]. The scenario will be completely different in European countries, Middle Eastern countries, North American countries, and the Indian subcontinent [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. A Chinese group also highlighted the need to focus resources on child safety and improve national knowledge of child abuse in China based on a systematic review [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese group also highlighted the need to focus resources on child safety and improve national knowledge of child abuse in China based on a systematic review [ 44 ]. A recent Turkish study [ 43 ] reported that, in sum, teachers’ knowledge levels concerning child neglect and abuse significantly increased after training. Therefore, the Turkish national education system should develop and implement an intervention program to assist teachers in identifying incidents of child neglect and abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for these low numbers may include a lack of appropriate recognition and knowledge of CAN, lower self-efficacy, indifference, and psychological barriers to reporting and responding to CAN as well as Japanese traditional norms regarding the family (e.g., family issues are private and should not be intervened in) [14,20,21]. Although training programs to acquire and improve their recognition, knowledge, and behaviors regarding CAN have been developed and implemented for health and educational professionals in previous studies [22][23][24][25], an effective training program focusing on citizens (CLs: laypersons) has not yet been developed. Social Cognitive Theory [26][27][28] suggests that increasing selfefficacy is essential to change behaviors, and it is influenced by the following four factors: enactive mastery experience, vicarious learning/modeling, verbal persuasion, and physical and psychological arousal.…”
Section: Introductionmentioning
confidence: 99%
“…Caring about students’ well-being and mental health, creating a school environment that is safe and trustworthy or taking time with each student to discuss emotions or provide strategies to foster resilience and post-traumatic growth are a few strategies that seem to work effectively and are usually embraced by trauma-sensitive schools [ 31 33 ]. Interventions that have been tested in this approach have promising effects in terms of improvements in teachers’ knowledge about child abuse and neglect [ 34 ], students’ school adjustment and mental health outcomes [ 35 ] and in the reduction of violent experiences [ 36 ]. Some studies have also found that training teachers in the prevention of child victimization enables students to progress in learning [ 37 ] and benefits the early learning skills of children and adolescents, improving the quality of the school environment [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Programs about child abuse addressed to teachers and studies performed with school staff [ 34 , 53 , 54 ] report that this population lack training to prevent, detect and intervene effectively when faced with victimization against children and adolescents. On the other hand, studies testing programs [ 55 ] including the victim’s voice [ 39 , 40 ] or the trauma-sensitive approach [ 36 , 56 ] have found positive effects at the school level (e.g., the reduction of violent incidents or improvements in the school climate) and the individual level (e.g., decreasing post-traumatic stress symptoms or increasing hope and school adjustment).…”
Section: Introductionmentioning
confidence: 99%